1999
DOI: 10.1677/joe.0.1630055
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy affects body composition and leptin differently in obese and non-obese postmenopausal women

Abstract: Leptin and oestrogen are both involved in the regulation of adipose tissue deposition and feeding behaviour. We investigated whether 5 years of hormone replacement therapy (HRT) affected serum leptin and body composition differently in 89 postmenopausal women treated with HRT compared with 178 controls. At baseline, leptin was significantly correlated with oestradiol (r=0·13, P<0·05) and in multiple backward regression analysis including oestradiol and any estimate of body fat, oestradiol remained a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 51 publications
4
54
2
Order By: Relevance
“…High leptin levels (independently of adiposity) shown in girls at the higher Tanner stage (30), were suggestive of the regulatory function of leptin on reproductive system (7,31,32). This hypothesis was supported by documentation of increasing leptin levels in late follicular phase of the normal menstrual cycle accompanied by an estrogen concentration that is twofold higher (33).…”
Section: Discussionmentioning
confidence: 89%
“…High leptin levels (independently of adiposity) shown in girls at the higher Tanner stage (30), were suggestive of the regulatory function of leptin on reproductive system (7,31,32). This hypothesis was supported by documentation of increasing leptin levels in late follicular phase of the normal menstrual cycle accompanied by an estrogen concentration that is twofold higher (33).…”
Section: Discussionmentioning
confidence: 89%
“…Numerous studies have indicated that HRT prevented or reduced weight gain [8][9][10][11][12][13][14][15]18 and android (central) fat accumulation. [8][9][10][11][12][13][14][15]18,19 Manolio et al 8 reported that estrogen users had lower weight, BMI, and WHR than subjects never treated. Espeland et al 9 showed that women randomly assigned to take conjugated equine estrogen (CEE) with or without a progestational agent averaged 1.0 kg less weight gain at the end of 3 y than those assigned to take placebo.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Many menopausal women believe that hormone replacement therapy (HRT) causes weight gain, 7 but whether this impression is correct remains uncertain. In fact, many clinical studies indicated that HRT prevented or reduced weight gain [8][9][10][11][12][13][14][15][16][17][18] and body fat gain, [8][9][10][11][12][13][14][15]18,19 although other investigators found the opposite both for weight 20,21 and body fat. 20,21 Thus, the effect of HRT concerning weight and body fat remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…For postmenopausal women, reports of body composition changes with and without hormone replacement therapy are conflicting [45,46]. Women with Turners syndrome have reduced lean body mass, which increases with oestrogen and gestagen therapy [18].…”
Section: Discussionmentioning
confidence: 99%